Influence of planting dates and pruning on the produccion of ocra(Abelmoschus esculentus) cultivars. - Díaz-Franco, Arturo; Ortegón, Alfredo S. (Agronomía Mesoamericana, 2016)
The production of five okra cultivars (Abelmoschus esculentus) during the regular planting season and after pruning was evaluated. Four hybrids and the variety ‘Clemson Spineless 80’ were tested in two planting dates during 1994 (Feb-15/Mar-22) and 1995 (Feb-21/Mar-15).At the end of the regular season, the stalks of the plants were cut 25 cm above the soil surface to measure the fruit after pruning. During the regular season, march planting dates showed precocity. Most of hybrids showed harvest precocity and larger fruit yields than ‘Clemson Spineless 80’ , ‘Cajun Delight’ registered the highest yield in both years. After pruning in 1994, hybrids were four days earlier precocious than the variety, and ‘Green Best’ and ‘North- South’ had the greatest yields in the two plantings dates. Additionals yields ranging from 10% to 76% were obtained by pruning .The planting date of Feb-15 was superior in the total yield. Pruning production in 1995 was affected by a high incidence of sweetpotato whitefly (Bemisia argentifolii) populations.